2015
DOI: 10.1007/s11095-015-1806-z
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Pharmacokinetics and Pulmonary Lymphatic Exposure of a Generation 4 PEGylated Dendrimer Following Intravenous and Aerosol Administration to Rats and Sheep

Abstract: The data suggest that rats provide a relevant model for assessing the pharmacokinetics of inhaled macromolecules prior to evaluation in larger animals, but that the pulmonary lymphatics are unlikely to play a major role in the absorption of nanocarriers from the lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 43 publications
2
25
1
Order By: Relevance
“…To ensure maximal delivery to the lung, the colistin and CMS formulations were nebulized via an endotracheal (ET) tube directly into the trachea, in a manner similar to that previously reported (54). Prior to administration, each animal was restrained and intubated with an ET tube (Smiths Medical, Bella Vista, NSW, Australia) (inner diameter [ID], 7.5 to 8 mm) via the nasal cavity using a fiber-optic endoscope (model FG-16X; Pentax, Montvale, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…To ensure maximal delivery to the lung, the colistin and CMS formulations were nebulized via an endotracheal (ET) tube directly into the trachea, in a manner similar to that previously reported (54). Prior to administration, each animal was restrained and intubated with an ET tube (Smiths Medical, Bella Vista, NSW, Australia) (inner diameter [ID], 7.5 to 8 mm) via the nasal cavity using a fiber-optic endoscope (model FG-16X; Pentax, Montvale, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The dendrimer containing the DGA-VCit linker was cleared ~2 fold slower than G4 PEG570-DGA-GLFG after IV administration, although terminal half-lives (approximately 1.5 days) were similar, indicating reductions in volume of distribution of a similar magnitude (Fig 2, Table 1). In contrast, a corresponding fully PEGylated construct (ie non-drug conjugated, G4 100% PEG 570 conjugated) reported previously, was cleared from plasma ~1.5 to 3 fold faster, although terminal half-life was similar (supporting information) 3 . These differences may reflect changes in the interaction of dendrimers with membranes and plasma proteins as a result of differences in the presentation or orientation of Dox which is extensively protein bound in plasma.…”
Section: Intravenous Pharmacokinetics and Biodistributionmentioning
confidence: 64%
“…Dendrimers were synthesised and characterised as described previously 9 , with modification (see supplementary information for synthetic details). 3 H-lysine was incorporated into the penultimate generation to enable pharmacokinetic characterisation of the dendrimer construct. The specific activity of the dendrimers was determined via scintillation counting 10 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that inhalation administration has an apparent advantage over oral administration in the treatment of certain diseases (Levet et al, 2017;Ryan et al, 2015). More significantly, Wattenberg & Coccia (1991) found that oral administration DL to mice could inhibit carcinogen-induced lung neoplasia.…”
Section: Introductionmentioning
confidence: 99%